Pediatric case of acute right-sided abdominal pain: diagnosis is not always appendicitis - Elgharbawy F; Salameh K; Al Rayes T; Abdelgadir IS (Dove Medical Press, 2017)
Fawzia Elgharbawy,1 Khalil Salameh,1 Talal Al Rayes,2 Ibtihal S Abdelgadir3 1Pediatrics Division, Al Wakra Hospital, 2Hamad Medical Corporation, 3Sidra Medical and Research Centre, Doha, Qatar Abstract: Omental infarction (OI) is a rare cause of acute abdominal pain occurring in 0.1% of children, which is typically diagnosed during surgery for suspected appendicitis. We present the case of a 7-year-old Pakistani girl. She presented with acute, severe, progressive, right-sided abdominal pain, which was present for 12 hours before presentation. No constitutional symptoms such as fever, anorexia, nausea or vomiting were present. Clinical examination revealed an adequately growing child following the 50th centile. She had severe generalized abdominal tenderness with rebound tenderness and guarding, mainly on the right lower abdominal quadrant, with all other system examinations normal. She had mildly increased inflammatory markers, and her initial abdominal ultrasound scan result was within normal limits. She had laparoscopic surgery following a diagnosis of suspected acute appendicitis; however, an intraoperative diagnosis of OI was made. This was later confirmed by histopathology. This case report highlights the importance of including OI in the differential diagnosis list of acute abdominal pain in children, in addition to the importance of computed tomography (CT) as the gold standard tool to aid diagnosis. In the presence of typical symptoms and signs of OI, a CT scan can assist and guide the management of similar cases. This course of action is suggested for the reason that OI typically runs a self-limited course and conservative care may be the most appropriate recommended course of action. Consequently, unnecessary operations could be avoided due to the diagnosis confirmation of studying images. Keywords: omentum, infarction, abdominal pain, child